Listening Comprehension Difficulties of EFL Students at the Faculty of Languages and Translation, Azzaytuna University - Adel Mohammad; Awatif Alsharf (AlQalam Journal of Medical and Applied Sciences, 2025)
This descriptive quantitative study identifies the listening comprehension difficulties encountered by English as a Foreign Language (EFL) students at the Faculty of Languages and Translation, Azzaytuna University. The research addressed a central question: What are the primary difficulties that hinder the development of listening skills? The study was conducted in the first semester of the 2023/2024 academic year with a sample of 41 students from all educational levels. Data were collected via a closed-ended questionnaire and analyzed using the Statistical Package for the Social Sciences (SPSS). The findings, confirmed by inferential statistical analysis, revealed significant challenges categorized into three areas: Listener-related difficulties, including limited vocabulary, insufficient practice, and problems with concentration; Listening material-related difficulties, such as unfamiliar accents, high-speed speech, and complex grammatical structures; and Physical setting-related difficulties, which encompassed poor audio quality, environmental noise, and crowded classrooms. Among these, issues with the physical learning environment were found to be the most severe. The study concludes that these multifaceted barriers significantly impede students’ listening proficiency. It is recommended that students adopt metacognitive strategies to become more aware of these challenges. Furthermore, university authorities must prioritize improving physical learning conditions through investment in better audio technology and infrastructure.